Euroregions as Soft Spaces: Between Consolidation and Transformation - Telle, Stefan (European Spatial Research and Policy, 2018)
National borders constitute barriers to social, economic and political processes and, thus, tend to contribute to the peripheralisation of border regions. The paper compares the evolution of two euroregions in peripheral central European border regions, whose objective is to overcome such negative border effects by promoting cross-border cooperation at the regional level. On a theoretical level, the paper argues for an understanding of euroregions as soft spaces. Rather than viewing them primarily as instances of state rescaling, the paper emphasizes their role as adaptive service providers for local constituencies. It is suggested that their long-term stability depends on their relation to, and the internal dynamics of, politico-administrative hard spaces at the regional, national, and supranational level. While hard spaces are associated with the notion of the Weberian bureaucratic state, soft spaces combine many of the ideas of the New Public Management literature. Building on an organizational ecology perspective, the paper forwards the argument that stable, resourceful, and accessible hard spaces constitute a predictable and engaging environment within which softer arrangements may compete for the delivery of services. However, the interplay between soft and hard spaces tends to have an impact on the euroregions’ agendas. While EU cohesion policy provides incentives to strengthen horizontal cross-border coordination, the organizational integration of the two euroregions remained rather loose, testifying to the continued importance of domestic prerogatives.